Effects of Open- and Closed-Label Nocebo and Placebo Suggestions on Itch and Itch Expectations - Meeuwis, Stefanie H.; van Middendorp, Henriët; van Laarhoven, Antoinette I.M.; Veldhuijzen, Dieuwke S.; Lavrijsen, Adriana P.M.; Evers, Andrea W.M. (Frontiers in Psychiatry, 2019)
Placebo and nocebo effects have been shown to influence subjective symptoms such as itch. These effects can be induced by influencing outcome expectations through, for example, combining the application of an inert substance (e.g., a cream) with verbal suggestions on the anticipated effects of this substance. Interestingly, placebo effects also occur when it is known that a treatment is inert (i.e. open-label placebo). However, no study to date has examined the efficacy of negative and positive verbal suggestions under similar open-label and closed-label (i.e. concealed placebo/nocebo) conditions in itch. A randomized controlled between-subjects study design was applied in which healthy volunteers (n=92) were randomized to I) an open-label positive verbal suggestions group, 2) a closed-label positive verbal suggestions group, 3) an open-label negative verbal suggestions group, or 4) a closed-label negative verbal suggestions group. Verbal suggestions were made regarding the topical application of an inert substance. Itch was evoked experimentally by histamine iontophoresis at baseline and again following suggestions. Itch expectations, self-reported itch during and following iontophoresis, and skin response parameters were measured. Positive suggestions were found to result in significantly lower expected itch compared to negative suggestions in both open- and closed-label conditions. No effects of the suggestions on itch during iontophoresis were found, but significantly lower itch was reported in the 4 minutes following iontophoresis in the (combined open- and closed-label) positive compared to the negative verbal suggestions groups. In addition, a smaller increase in skin temperature was found in the positive compared to the negative suggestions groups. The findings illustrate a potential role of (open- and closed-label) placebo for optimizing expectations and treatment effects for itch in clinical practice.